Adherence with infection prevention and control measures among Italian healthcare workers: Lessons from the COVID-19 pandemic to tackle future ones - Francesca Licata; Caterina Viscomi; Silvia Angelillo; Gianfranco Di Gennaro; Aida Bianco (Elsevier, 2024)
Background: To tackle future health threats, the study aimed to assess healthcare workers' (HCWs) adherence to infection prevention and control (IPC) measures and to evaluate whether knowledge and concerns related to COVID-19 could be its potential predictors. A secondary aim was to explore how and how much healthcare facilities support HCWs to implement IPC practices. Methods: This cross-sectional study was conducted between June and September 2021 in Southern Italy using a self-administered questionnaire. Socio-demographic and professional characteristics, COVID-19 preparedness and response plan in the facilities, knowledge about COVID-19's transmission and non-pharmaceutical interventions (NPIs), concerns about the possibility of transmitting COVID-19 to family members and patients, adherence to IPC practices, and sources of information were investigated. Results: Among the 492 enrolled HCWs, the overall knowledge median score was 6 out of a maximum score of 8 and predictors of good knowledge were practicing in a facility that organized training courses about IPC measures and having more years in practice. HCWs were more concerned about the possibility of transmitting the infection to their family members (64.4%) than to negative patients (38.9%). A sizable proportion claimed to take off the face mask by touching only the straps or ties (76.3%) and to replace the face mask when it was wet (70.7%). Only 26.2% never/rarely touched the face mask while wearing it. Good adherence to preventative practices was more likely in HCWs other than physicians and practicing in a facility that organized training courses about IPC measures and in regional hospitals compared with those practicing in district hospitals. Conclusions: The study findings produce information about what worked well and where gaps were identified during COVID-19 pandemic, along with data useful for hospitals and health systems in general to better prepare and put in place appropriate interventions in case of similar future events.